Mangrove carbon and nutrient accumulation shifts driven by rapid development in a tropical estuarine system, northeast Brazil. (May 2021) - Passos, Tiago; Penny, Dan; Sanders, Christian; De França, Elvis; Oliveira, Thais; Santos, Luciana; Barcellos, Roberto
Abstract: Mangrove environments are important for maintaining biodiversity and carbon cycling. However, these systems are being degraded at alarming rates around the world, particularly in rapidly developing regions. Here, we examine a sediment profile from a mangrove forest near a large port complex at Suape, northeast Brazil, in order to assess the impact of rapid urbanization and industrialization. We find that total organic carbon (TOC) and total nitrogen (TN) accumulation rates have increased in the estuary since the 1980's, directly related to rapid urban development. The TN and heavy δ 15 N values in the sediment column suggest increasing anthropogenic influences. In contrast, heavy metal fluxes did not increase during these transitions. The increase in TOC and TN accumulation rates during the past four decades highlight the significant role mangrove areas play as sinks for anthropogenically enhanced nutrients in poorly-understood tropical areas. Highlights: TOC and TN accumulation rates have increased in the estuary since the 1980's reflecting urbanization and industrial growth. The TN increase and heavy δ 15 N values in the sediment column in the last decades suggests increasing anthropogenic impact. Heavy metal fluxes did not change during these transitions. This study shows the significant role of mangroves as sinks for anthropogenically enhanced nutrients in tropical areas.